2010
DOI: 10.1029/2010gl043679
|View full text |Cite
|
Sign up to set email alerts
|

Depth‐dependent activity of non‐volcanic tremor in southwest Japan

Abstract: With a new location method, we obtained a high‐resolution map of non‐volcanic tremor along the subducting Philippine Sea plate in southwest Japan and clarified the depth‐dependent behavior of the tremor activity. A bimodal distribution of tremor along‐dip is apparent in regions where short‐term slow slip events (SSEs) and very‐low‐frequency earthquakes are frequently detected. The separation of bimodal peaks is 5 to 10 km in depth. The updip tremor activity occurs episodically, coincident with major bursts tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
213
2

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(237 citation statements)
references
References 28 publications
22
213
2
Order By: Relevance
“…In Shikoku, several peaks are identified at periods around 6.6 to 6.8 (approximately 50 to 80 days) and 6.95 (approximately 100 days), corresponding to the recurrence intervals on the downdip and updip parts of the subducting slab, respectively. The recurrence interval of the updip part of tremor activity in Shikoku (approximately 100 days) and it bimodal distribution is roughly consistent with Obara et al (2010). A short-term peak of 50 to 80 days is less prominent for Kii-Tokai, and this is also consistent with the observations of Obara et al (2010).…”
Section: Regional and Global Variations In Temporal Clustering Propersupporting
confidence: 79%
See 3 more Smart Citations
“…In Shikoku, several peaks are identified at periods around 6.6 to 6.8 (approximately 50 to 80 days) and 6.95 (approximately 100 days), corresponding to the recurrence intervals on the downdip and updip parts of the subducting slab, respectively. The recurrence interval of the updip part of tremor activity in Shikoku (approximately 100 days) and it bimodal distribution is roughly consistent with Obara et al (2010). A short-term peak of 50 to 80 days is less prominent for Kii-Tokai, and this is also consistent with the observations of Obara et al (2010).…”
Section: Regional and Global Variations In Temporal Clustering Propersupporting
confidence: 79%
“…The recurrence interval of the updip part of tremor activity in Shikoku (approximately 100 days) and it bimodal distribution is roughly consistent with Obara et al (2010). A short-term peak of 50 to 80 days is less prominent for Kii-Tokai, and this is also consistent with the observations of Obara et al (2010). Peaks at around 4 to 6 months for Kii-Tokai likely reflect variable recurrence intervals along the strike of the subducting slab, corresponding to the along-strike segmentation of short-term slow-slip events (Sekine et al 2010).…”
Section: Regional and Global Variations In Temporal Clustering Propersupporting
confidence: 55%
See 2 more Smart Citations
“…Yet knowledge of the upper crust is not in itself sufficient to characterize seismic hazard, as lower crustal slip beneath the seismogenic zone can drive the seismicity in the upper crust (Tse and Rice, 1986;Scholz, 2002) and lead to the nucleation of large earthquakes (Nadeau and Guilhem, 2009;Shelly, 2009;Segall and Bradley, 2012). Low Frequency Earthquakes (LFEs), which accompany the slow slip events observed on the deep extension of fault interfaces in Cascadia (Rogers and Dragert, 2003;Bostock et al, 2012), Japan (Obara et al, 2004;Shelly et al, 2006), and Mexico (Rivet et al, 2011;Frank et al, 2013), have also been observed in the Parkfield region of California (Nadeau and Dolenc, 2005;Shelly et al, 2009), and present the opportunity to illuminate the elusive elastic and slip behaviors of the lower crust (Rubinstein et al, 2010).…”
Section: Introductionmentioning
confidence: 99%